2007
DOI: 10.1111/j.1468-3083.2006.02039.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of familial erythromelalgia with venlafaxine

Abstract: 5 Hesse S, Berbis P, Privat Y. Keratoderma palmoplantaris papulosa (Bushcke-Fischer's disease): efficacy of acitretin. Br J Dermatol 1993; 128: 104 -105. 6 Horikoshi M, Kuroda K, Tajima S. Puncate palmoplantar keratoderma with pigmentary lesions on the dorsa of feet and ankles: successful treatment with a combination of low-dose oral etretinate and topical calcipitriol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In contrast, preliminary results in PE indicate low or absent effectivity of this drug (62). Moreover, in those cases in which lidocaine or mexiletine are helpful in PE, the efficacy of these agents is only partial or transient (63).…”
Section: Implications For New Therapeutic Approaches To Painmentioning
confidence: 77%
“…In contrast, preliminary results in PE indicate low or absent effectivity of this drug (62). Moreover, in those cases in which lidocaine or mexiletine are helpful in PE, the efficacy of these agents is only partial or transient (63).…”
Section: Implications For New Therapeutic Approaches To Painmentioning
confidence: 77%
“…1,89 Sixty percent of children with SCN9A-positive IEM identified by systematic review, and 3 of 4 cases at our center, had significant peripheral tissue injury secondary to prolonged cold immersion or rubbing/scratching. Prolonged ice immersion and/or environmental cooling have been associated with severe hypothermia requiring intensive care; 40,70,74,75,79 skin injury with sepsis and significant morbidity; 3,31,48,90,91 and mortality. 49,55,61,90 The extent to which hypertension 50 and increased plasma or urine catecholamines 44,92 in pediatric IEM cases are secondary to uncontrolled pain and stress is difficult to determine.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,16,33,50,56,[59][60][61][62][63][64][65][66][67][68] SCN9A-related IEM cases in adults reporting onset of symptoms before 18 years are also listed (Table 2B; online). 2,3,6,17,18,33,48,61,63,[69][70][71][72][73][74][75][76][77][78][79][80][81][82] Overall, pediatric onset IEM was associated with 24 different Na v 1.7 channel substitutions. As in the systematic review, additional cases reported major complications associated with excessive cooling or ice immersion: skin injury and sepsis resulting in amputations (p.L858F) 78 and mortality (p.F216S); 61,70 and severe hypothermia (p.L858F 78 ) with associated cerebral symptoms (p.I848T, 75 p.F216S 70 ) (Table 2B; online).…”
Section: Descriptive Synthesis Of Systematic Literature Reviewmentioning
confidence: 99%
“…Selective serotonin and norepinephrine reuptake inhibitors such as fluoxetine, sertraline, and venlafaxine have also been used with reported remission 53,54. Serotonin antagonists such as methysergide and pizotifen have been tried with some reported effectiveness 110,111.…”
Section: Pharmacotherapymentioning
confidence: 99%